ARTMAP-FUZZY: INTELLIGENT SYSTEM APPLIED TO FAULT DETECTION IN A TRACTOR - da Silva, F. D. G.; Chavarette, F. R.; Lopes, M. L. M. (Revista Brasileira de Engenharia de Biossistemas, 2016)
This paper presents the development of an intelligent system that, by an artificial neural network, works in the detection of structural flaws in a tractor. It was simulated a tractor by means of a numerical model built by differential equations, which generates data as to change the speed and the distance between the protrusions on the ground. For the analysis, identification and characterization of computationally simulated data was encoded a system that utilizes concepts of Adaptive Resonance Theory present in the ARTMAP-fuzzy neural network. The main objective of this system is to inspect the tractor structure contributing to its better conservation, indicating whether it is in normal conditions or structural failure situation. The results obtained in the application of neural network to the specified problem proved to be efficient and accurate.